TAX EVASION IN ROMANIA - THE INFLUENCE OF THE VAT GAP ON THE DEGREE OF TAX REVENUE COLLECTION - GUIU MARIAN-ROMEO (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Currently, tax evasion is the most important component of the mechanism of economic-financial crime, and the EU space is faced with an impressive dynamic of the export and import of economic crime, combating this phenomenon becoming the primary goal of specialized bodies, since in essence, evasion fiscal refers to the action of avoiding or evading the payment of taxes and duties to the state. Certain case studies and recent researches at the international level have highlighted the fact that Romania, compared to other EU states, has a gap to recover in terms of tax collection, especially the VAT GAP, which indicates a low degree of compliance with the payment of this tax. In the context of the accentuation of the budget deficit caused to a large extent by the degree of collection of fees and taxes owed by taxpayers, we consider the current topic, the purpose of this paper is to explore whether the increase in the degree of collection of fees and taxes can be influenced by certain factors such as the level of economic development, the existence of a correct compliance environment, the perceived trust in the tax authorities compared to the corruption perception index registered by Romania.